LEVEL OF BELARUSIAN INNOVATION POTENTIAL DEVELOPMENT - N. P. Chetyrbok (Наука и техника)
The paper gives analysis of the Belarusian innovation potential development which includes an investigation of state and tendencies in development of scientific, technical and technological potentials, analysis of innovation infrastructure and state mechanisms of innovation activity stimulation. A special attention is given to formation and realization of a regional innovation policy. The paper considers theoretical aspects of the given process and contains definition of the given aspect and concept of strategic management of innovation region development.